2019
DOI: 10.1080/15732479.2019.1687528
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of the inspection intervals on the track geometry condition

Abstract: In order to evaluate the railway track geometry condition and plan maintenance activities, track inspection cars run over the track at specific times to monitor it and record geometry measurements. Applying an adequate inspection interval is vital to ensure the availability, safety and quality of the railway track, at the lowest possible cost. The aim of this study has been to investigate the effect of different inspection intervals on the track geometry condition. To achieve this, an integrated statistical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…Traditionally, TG parameters are measured by the dedicated TG inspection systems in regular inspections, which are typically based on high-value laser triangulation sensors or/and inertial measurement units (IMU). The inspection interval is usually defined as several months, which results in the lack of up-to-date information on track conditions [11]. In order to improve the information availability and enable efficient maintenance decisions, TG monitoring on in-service vehicles was proposed.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Traditionally, TG parameters are measured by the dedicated TG inspection systems in regular inspections, which are typically based on high-value laser triangulation sensors or/and inertial measurement units (IMU). The inspection interval is usually defined as several months, which results in the lack of up-to-date information on track conditions [11]. In order to improve the information availability and enable efficient maintenance decisions, TG monitoring on in-service vehicles was proposed.…”
Section: Background and Motivationmentioning
confidence: 99%
“…When the degradation path exceeding the threshold is deemed as a defect, track condition can be classified as normal and defected states, and logistic regression by its nature is suitable in solving this problem, cf. Andrade and Teixeira (2014), Nissen (2019), Sharma, Cui, He, Mohammadi, and and Soleimanmeigouni et al (2019). Survival analysis is widely used to model the uncertainty in system lifetimes.…”
Section: Statistical Approachmentioning
confidence: 99%
“…In order to consider the UH2 defects in the optimization model, it is necessary to predict the probability of the occurrence of UH2 defects in track section sS in maintenance window t, i.e., P s, t : It has been shown that the probability of the occurrence of severe isolated defects is dependent on the typical track geometry indicators used to plan maintenance activities, e.g. the SDLL (Andrade & Teixeira, 2014;Soleimanmeigouni, Ahmadi, Khajehei & Nissen, 2020).…”
Section: Modelling the Probability Of Uh2 Defectsmentioning
confidence: 99%